Ketidakpaduan Paragraf : Penggunaan Alat Kohesi pada Majalah Larise Edisi November 2024 - Septia Tri Astutiningsih; Mariska Arsyana Putri; Sri Muryati (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the inconsistency of paragraphs in articles published in the November 2024 edition of Larise magazine. The approach used in this study is qualitative descriptive with data collection methods in the form of observation and recording. The results of the analysis revealed that the incongruity of the paragraphs was caused by several factors, such as the lack of transitional sentences, irregular order of details, and unnecessary repetition of words. Although some paragraphs have implemented the cohesion element correctly, some sections still struggle to connect ideas effectively, making it difficult for readers to follow the flow of the article. These findings show the importance of increasing the use of cohesion techniques to make texts more structure and easy to understand. Magazine writers and editors are advised to improve the application of cohesion elements to improve the cohesion of the text and make it easier for readers to follow the flow of thought. Thus, this study contributes to a deeper understanding of the application of cohesion techniques in print media writing and highlights the need for improvement in these areas to achieve more effective communication. Keywords: cohesion; paragraph incompatibility; majalah larise